The impact of CEOs’ academic backgrounds on corporate financialization - Bao Qi; Fan Hu; Chen Zhang (PLoS ONE, 2026)
While prior research has examined macroeconomic drivers of corporate financialization, little is known about how top executives’ personal traits shape this phenomenon. Drawing on imprinting theory, this study investigates whether and how CEOs’ academic backgrounds influence corporate financialization. Using data from Chinese A-share non-financial listed companies (2010–2022), we employ multiple regression analyses to test the relationships and underlying mechanisms. The results show that CEOs with academic backgrounds significantly reduce corporate financialization, particularly in non-state-owned enterprises and firms with lower analyst coverage. Further analysis using a mediating effect model indicates that managerial myopia and physical capital investment partially mediate the relationship between CEOs’ academic backgrounds and corporate financialization. These findings fill an important gap in the literature by revealing a micro-level behavioral channel that complements macro-level explanations of financialization. The study extends imprinting theory by identifying academic experience as a distinctive managerial imprint that shapes ethical and long-term financial decision-making, and it provides practical implications for executive selection, governance improvement, and sustainable corporate development in emerging markets.